1985
DOI: 10.1252/jcej.18.248
|View full text |Cite
|
Sign up to set email alerts
|

Gas holdup and volumetric liquid-phase mass transfer coefficient in solid-suspended bubble column with draught tube.

Abstract: The effects of column dimensions, gas velocity and properties of the liquid and the solid particles on the gas holdup sG and the volumetric liquid-phase mass transfer coefficient kLa in a solid suspended bubble column with a draught tube and a conical bottom were studied experimentally in a liquid-solid batch operation. The presence of suspended solid particles in the column reduces the values of eG and kLa, and their reduction due to the addition of solid particles to the column increases with increasing soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 5 publications
10
38
2
Order By: Relevance
“…The observed dependence of gas hold-up on the solid hold-up is consistent with that experimentally found in a similar system by Koide et al (1985), who reported that the gas hold-up decreases with increasing solid concentration for the case of glass beads ( S ‫ס‬ 2500 kg/m 3 ) and bronze spheres ( S ‫ס‬ 8770 kg/m 3 ). Also, in the case of solids of lower density, gas hold-up was found to decrease with increasing solid loading, as reported by Miyahara and Kawate (1993) for plastic beads ( S ‫ס‬ 1043 to 1135 kg/m 3 ), by Hwang and Lu (1997) for polystyrene cylinders ( S ‫ס‬ 1050 kg/m 3 ), and by Lu et al (1995) for calcium-alginate beads ( S ‫ס‬ 1030 kg/m 3 ).…”
Section: Gas Hold-upsupporting
confidence: 91%
See 2 more Smart Citations
“…The observed dependence of gas hold-up on the solid hold-up is consistent with that experimentally found in a similar system by Koide et al (1985), who reported that the gas hold-up decreases with increasing solid concentration for the case of glass beads ( S ‫ס‬ 2500 kg/m 3 ) and bronze spheres ( S ‫ס‬ 8770 kg/m 3 ). Also, in the case of solids of lower density, gas hold-up was found to decrease with increasing solid loading, as reported by Miyahara and Kawate (1993) for plastic beads ( S ‫ס‬ 1043 to 1135 kg/m 3 ), by Hwang and Lu (1997) for polystyrene cylinders ( S ‫ס‬ 1050 kg/m 3 ), and by Lu et al (1995) for calcium-alginate beads ( S ‫ס‬ 1030 kg/m 3 ).…”
Section: Gas Hold-upsupporting
confidence: 91%
“…The influence of the presence of solids has been reported for various types of particles including glass beads (Koide et al, 1985), plastic beads (Miyahara and Kawate, 1993), polystyrene cylinders (Hwang and Lu, 1997), activated carbon particles (Muroyama et al, 1985) Raney nickel particles (Gavroy et al, 1995), and calcium-alginate beads (Lu et al, 1995). For the case of biofilm-coated particles, Ryhiner et al (1986) reported that the gas-liquid volumetric mass transfer coefficient in a three-phase biofilm fluidized sand-bed reactor decreased (in the range 0.02 to 0.04 s −1 ) with increasing amounts of clean sand and was almost independent of the sand fraction with biofilm-covered sand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…number of small bubbles produced in the riser had an insufficient bubble rise velocity to escape from the liquid. A similar trend was observed by Koide et al (1985), Nicol and Davidson (1988) and Al-Masry and Dukkan (1997).…”
Section: Variation Of Gas Holdup In the Riser With Superficial Gas Vesupporting
confidence: 87%
“…Correlations for gas holdup in slurry bubble columns have been proposed by a number of researchers including Decker et al (1980), Koide et al (1984), Sada et al (1986), Sauer…”
Section: Introductionmentioning
confidence: 99%